Fabricating Surface-Functionalized CsPbBr3/Cs4PbBr6 Nanosheets for Visible-Light Photocatalytic Oxidation of Styrene - Qiu, Ping; Wang, Qiuhe; Zhao, Yizhou; Dai, Yi; Dong, Yuanyuan; Chen, Changli; Chen, Qi; Li, Yujing (Frontiers in Chemistry, 2020)
The halide perovskite (PVSK) material, an excellent light absorber with fast carrier kinetics, has received increased attention as a potential photocatalyst for organic synthesis. Herein, we report a straightforward synthesis of chemically modified halide perovskite and their application as efficient photocatalysts to convert styrene into benzaldehyde. A simple method is employed to synthesize the chemically modified CsPbBr3/Cs4PbBr6 nanosheets by using ZrCl4 to simultaneously achieve the Cl-doping and the surface modification with Zr-species. The photocatalytic oxidation rate of styrene to benzaldehyde catalyzed by surface-modified CsPbBr3/Cs4PbBr6 nanosheets under visible light can reach 1098 μmol g-1 h-1, 2.9 times higher than that of pristine CsPbBr3/Cs4PbBr6 nanosheets (372 μmol g-1 h-1). The enhanced photocatalytic performance may originate from the modified band structure induced by the synergistic effect of Cl-doping and surface modification, whereby the same methodology can be applied to MAPbBr3. This work demonstrates the surface modification of PVSK materials and their potential as efficient photocatalyst towards the organic synthesis.